Ultra-processed foods and allergic symptoms among children and adults in the United States: A population-based analysis of NHANES 2005–2006 - Kong, Weiliang; Xie, Yilian; Zhong, Jingjing; Cao, Chao (Frontiers in Public Health, 2022)
Design There is a strong correlation between dietary intake and allergic diseases. Ultra-processed foods (UPFs) are gradually becoming dominant worldwide and causing health problems for children and adults. We hope to determine whether links exist between UPFs and allergic symptoms. Methods We investigated data from 2,736 children (16–19 years) and 4,256 adults (≥20 years) from the National Health and Nutritional Examination Survey (NHANES) 2005–2006. The associations between the mean UPFs contribution to total energy intake and all allergic symptoms (IgE, current asthma, allergy, rash, sneeze, wheeze, eczema, and hay fever) were estimated by weighted multivariate logistic regression. Results Logistic regression analysis showed UFPs were negatively associated with IgE levels in children. Those with higher quartiles had a reduced risk from 16% (OR, 0.84, 95%CI, 0.55 to 1.28) to 34% (OR, 0.66, 95%CI, 0.49 to 0.89), p for trend = 0.006. UPFs were also positively related to current asthma in children with an increased risk of 11% (OR, 1.11, 95%CI, 0.79 to 1.56) to 76% (OR, 1.76, 95%CI, 1.10 to 2.82), p for trend = 0.0393. UPFs were also associated with eczema in girls. But there was no association observed between UPFs and allergic symptoms in adults. Conclusion Our results suggested that UPFs assessed by the NOVA system were associated with IgE, current asthma in children, and eczema in girls. These results further support the need to test the association of modern dietary patterns with allergic symptoms.